2008
DOI: 10.1007/s10616-008-9124-5
|View full text |Cite
|
Sign up to set email alerts
|

A role for Drosophila in understanding drug-induced cytotoxicity and teratogenesis

Abstract: Drosophila research has been and continues to be an essential tool for many aspects of biological scientific research and has provided insight into numerous genetic, biochemical, and behavioral processes. As well, due to the remarkable conservation of gene function between Drosophila and humans, and the easy ability to manipulate these genes in a whole organism, Drosophila research has proven critical for studying human disease and the physiological response to chemical reagents. Methotrexate, a widely prescri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…In addition, DES has been reported to have advantageous bioprocess characteristics, such as high cell density attained, low cost culture medium needed and continuous bioprocess possibility (Affleck and Walker, 2008;Batista et al, 2008Batista et al, , 2009Bovo et al, 2008;Brillet et al, 2008;Galesi et al, 2008;Iwaki and Castellino, 2008;Jorge et al, 2008;Park et al, 2008;Santos et al, 2007;Swiech et al, 2008aSwiech et al, , 2008b. In previous publications Yokomizo et al, 2007) we have shown that the DES indeed represents a novel and promising approach for the production of the rabies virus glycoprotein (RVGP).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, DES has been reported to have advantageous bioprocess characteristics, such as high cell density attained, low cost culture medium needed and continuous bioprocess possibility (Affleck and Walker, 2008;Batista et al, 2008Batista et al, , 2009Bovo et al, 2008;Brillet et al, 2008;Galesi et al, 2008;Iwaki and Castellino, 2008;Jorge et al, 2008;Park et al, 2008;Santos et al, 2007;Swiech et al, 2008aSwiech et al, , 2008b. In previous publications Yokomizo et al, 2007) we have shown that the DES indeed represents a novel and promising approach for the production of the rabies virus glycoprotein (RVGP).…”
Section: Introductionmentioning
confidence: 99%
“…Cell culture systems are dynamic in their growth where the 2D and 3D systems help to study and understand cellular and molecular mechanisms with ease when compared to the complex animal models. These in vitro tools help researchers analyse and explore human cells to evaluate nanotoxicity in situations where an in vivo human model assessment is not possible [15,16]. However, the results obtained in in vitro studies are incomplete and not holistic as the data obtained from cell culture studies depend on the various cell growth and differentiation parameters that vary significantly from "within the flask" as compared to "within the body."…”
Section: Drosophila As a Model For Toxicity Assessmentmentioning
confidence: 99%
“…The data obtained are qualitative in the perspective that the genes that influence or direct loss of viability are not evaluated. Many molecular genetic studies in Drosophila have led to advances in investigating the lifecycle and development profile of the genes influencing them [15,16].…”
Section: Drosophila As a Model For Toxicity Assessmentmentioning
confidence: 99%
“…MTX elicits skeletal defects and developmental abnormalities in the fetus, which conflict with its use in chemotherapy. The Walker lab has exploited the high degree of conservation of DHFR and folate metabolism in the fly to screen for MTX-resistant variants of DHFR in a laboratory selection paradigm [3]. Interestingly, MTX elicits analogous defects on gestation and embryogenesis in the fly, causing reduction of egg production in females with corresponding deformities in the ovaries and a variety of embryonic defects in the progeny [4].…”
Section: Examples Of Measurable Endpoints In Drosophila Toxicologymentioning
confidence: 99%